Customer’s Perception Towards E-Service Quality In Malaysia’s Homestay Industry - Chin, Pui San (Universiti Malaysia Sarawak (UNIMAS), 2016)
The objective of this study is to determine the influence of the e-service quality in the context of homestay industry in Malaysia and to determine the effect of e-service quality dimensions on the overall e-service quality, customer satisfaction and behavioural intention. The theories that are adopted in this study are Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT). There are total of 250 questionnaires are distributed through both online and paper-based questionnaires. Firstly, multiple of e-service dimension are developed based on past studies and the concepts of each dimension is being examined. Furthermore, the relationships between each of the dimension are being examined as well. Then followed by an examination of the validity and reliability of each of the measuring instruments. The findings of this study is all the dimensions have relatively significant relationship effect on affecting the e-service quality, customer satisfaction and behavioural intention especially responsiveness, trust and personalization. In addition, there is a positive relationship between overall e-service quality, customer satisfaction and behavioural intention. This study also indicated that customer satisfaction is a mediator has indirect relationship to the overall e-service quality and behavioural intentions.